Hybrid Films of Graphene and Carbon Nanotubes for High Performance Chemical and Temperature Sensing Applications. Issue 28 (25th March 2015) - Tung, Tran Thanh; Pham‐Huu, Cuong; Janowska, Izabela; Kim, TaeYoung; Castro, Mickael; Feller, Jean‐Francois
<x xml:space="preserve">Abstract</x> A hybrid composite material of graphene and carbon nanotube (CNT) for high performance chemical and temperature sensors is reported. Integration of 1D and 2D carbon materials into hybrid carbon composites is achieved by coupling graphene and CNT through poly(ionic liquid) (PIL) mediated‐hybridization. The resulting CNT/PIL/graphene hybrid materials are explored as active materials in chemical and temperature sensors. For chemical sensing application, the hybrid composite is integrated into a chemo‐resistive sensor to detect a general class of volatile organic compounds. Compared with the graphene‐only devices, the hybrid film device showed an improved performance with high sensitivity at ppm level, low detection limit, and fast signal response/recovery. To further demonstrate the potential of the hybrid films, a temperature sensor is fabricated. The CNT/PIL/graphene hybrid materials are highly responsive to small temperature gradient with fast response, high sensitivity, and stability, which may offer a new platform for the thermoelectric temperature sensors.